Mutations in the Escherichia coli fnr and tgt genes: control of molybdate reductase activity and the cytochrome d complex by fnr. - Frey, B (1989)
In eubacteria, the tRNA transglycosylase (Tgt) in specific tRNAs exchanges a guanine in the anticodon for 7-aminomethyl-7-deazaguanine, which is finally converted to queuosine. The tgt gene of Escherichia coli has been mapped at 9 min on the genome, and mutant pairs containing an intact or mutated tgt allele were obtained after transduction of the tgt locus by P1 bacteriophages into a genetically defined E. coli strain (S. Noguchi, Y. Nishimura, Y. Hirota, and S. Nishimura, J. Biol. Chem. 257:6544-6550, 1982). These tgt mutants grew anerobically with fumarate as an electron acceptor, while nitrate or trimethylamine N-oxide could not be reduced. Furthermore, molybdate reductase activity was almost lacking and the characteristic absorption maxima, corresponding to cytochrome a1 and the cytochrome d complex, were not detectable in low-temperature reduced-minus-oxidized difference spectra in anaerobically grown cells. Transduction of the mutated tgt locus into another E. coli recipient resulted in tgt mutants without anaerobic defects. Transformation of the original tgt mutants with an fnr gene-containing plasmid reversed the anaerobic defects. Clearly, the original tgt mutants harbor a second mutation, affecting the anaerobic regulator protein Fnr. The results suggest that fnr is involved in anaerobic control of components of the cytochrome d complex and of the redox system that transfers electrons to molybdate. F' plasmids containing a fused lacI-lacZ gene with the nonsense codon UAG at different positions in the lacI part were transferred to E. coli strains with a mutated or nonmutated tgt locus but intact in fnr. A twofold increase in the frequency of incorrect readthrough of the UAG codon, dependent on the codon context, was observed in the tgt mutant and is suggested to be caused by a tRNA(Tyr) with G in place of queuosine.